INVESTMENTS AND RELATED INVESTMENT DECISIONS - Kurbonov Sanjar Sobir Ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article covers the essence of investments, their role in economic development and the process of making investment decisions associated with them. It examines in detail factors such as investment types, risks and expected rate of return. The article also analyzes methods for evaluating investment projects